2010
DOI: 10.1021/ol100776x
|View full text |Cite
|
Sign up to set email alerts
|

Anion Complexation by Triazolium “Ligands”: Mono- and Bis-tridentate Complexes of Sulfate

Abstract: By utilizing click chemistry and methylation, the triazolium motif was employed to design tridentate "ligands" that bind by electron acception instead of electron donation. As electronically inverted ligands they are able to complex sulfate ions by hydrogen bonding and electrostatic interactions. The formation of mono- or bis-tridentate complexes could be achieved by controlling the degree of methylation with the appropriate reagents and was proven by NMR spectroscopy and computational methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 23 publications
2
67
0
1
Order By: Relevance
“…Several seminal studies have demonstrated the ability of acyclic and macrocyclic bis- and poly(triazole) containing systems to bind anions in organic solvents through triazole C–H···anion interactions [47]. More recently, we [8], and others [910], have shown that alkylating the triazole group to give the triazolium group increases the strength of anion binding significantly by further polarising the C–H bond of the heterocycle.…”
Section: Introductionmentioning
confidence: 99%
“…Several seminal studies have demonstrated the ability of acyclic and macrocyclic bis- and poly(triazole) containing systems to bind anions in organic solvents through triazole C–H···anion interactions [47]. More recently, we [8], and others [910], have shown that alkylating the triazole group to give the triazolium group increases the strength of anion binding significantly by further polarising the C–H bond of the heterocycle.…”
Section: Introductionmentioning
confidence: 99%
“…While there are several classes of anion receptors containing neutral NH groups including ureas, thioureas, amides, pyrroles, imidazoles and indoles, 611 exclusive fluoride receptors that selectively recognize fluorides over other halides are indeed rare. 6 In most cases, such receptors bind other anions also, thereby hampering the selectivity for fluoride.…”
mentioning
confidence: 99%
“…3 Therefore, an increasing attention has recently been devoted to sulfate binding with synthetic receptors which include polyamines, 4 polyamides, 5 ureas, 6 indoles, 7 self-assembled metal–organic hosts, 8 and triazolium hosts. 9 The oxygen atoms in oxoanions are generally coordinated with two hydrogen bonds, thus sulfate with four oxygens is often found to be octacoordinated with synthetic receptors. 5a,10 Custelcean et al have shown that a tren-based urea linked with Ag 2 SO 4 is capable of binding a sulfate by twelve hydrogen bonds ( d N ··· O = 2.8516 to 3.1741 Å), 8a which is consistent with Hay’s prediction that each oxygen could be involved in a maximum of three hydrogen bonds.…”
mentioning
confidence: 99%